Formulation and characterization of choline fenofibrate sustained release capsule - Jain, Nidhi; Jain, Rohit; Dangi, Surendra (Journal of Drug Delivery and Therapeutics, 2018)
The drug ABT-335 (Fenofibricacid ) choline fenofibrate found to be useful in the treatment of dyslipidemia as compare with other fibrate. So the present investigation to developed mini-tablets to overcome the dose dumping problem by regular shape, uniformity, smooth surface excellent size and encapsulated in capsule to improve the efficacy and bioavailability of the drug. Different formulations were developed by utilizingcontrolling of the release rate and gel forming polymers like microcrystalline cellulose, hypromellose by dry granulation technique. Among all formulation SRM-3 having the drug release for longer period of time as compare to other formulation. SRM-3 was found to be stable during stability study for one month.Keywords: ABT-335 (Fenofibric acid) choline fenofibrate, like microcrystalline cellulose, hypromellose, sustained release matrix tablet.